Tensile and compressive performances of foam core sandwich composites with various core modifications. (January 2017) - Yalkin, Huseyin E; Icten, Bulent M; Alpyildiz, Tuba
The objective of this study is to enhance the out-of-plane tensile and compressive performances of foam core sandwich composite via structural core modifications considering the ease of application and time consumption. The performances of single core perforated, single core stitched, divided core perforated, and divided core stitched sandwich composites are compared with each other and reference plain foam core sandwich composites. Results indicate that "perforated and stitched core" sandwich composites have superior strength, and in terms of performance modification, dividing the core is found very efficient for plain (non-perforated and non-stitched) core sandwich composites.